South Korea's Interests behind the Reactivation of IK-CEPA Negotiations with Indonesia - Ulim Maidatul Cholif; Arie Kusuma Paksi (Insignia: Journal of International Relations, 2022)
Indonesia-Korea Comprehensive Economic Agreement Partnership (IK-CEPA) is a lengthy bilateral agreement. Negotiations were terminated in 2014 due to a discrepancy in the agreement between the Korean and Indonesian governments. Then, in 2018, Korea agreed to reactivate the IK-CEPA agreement in response to the Indonesian government's request. This paper analyzes the reasons behind South Korea's foreign policy in deciding to reactivate the IK-CEPA. The author uses the concept of National Interest to identify Korean foreign policy decision-making. A qualitative descriptive approach is used to uncover data about the phenomena. The author examines data from books, journals, government data, and reliable online articles. Then, summarize and evaluate all the relevant facts. Research shows that Korea's policy to reactivate the IK-CEPA agreement is based on South Korea‘s desire to achieve a trade surplus while expanding investment finance in Indonesia.